ROTATIONAL VARIATION OF THE MAGNETIC FIELD OF Β CrB IN DIFFERENT SPECTRAL LINES - Butkovskaya, V.; Baklanova, D.; Han, I.; Kim, K. M.; Lyashko, D.; Mkrtichian, D.; Plachinda, S.; Valyavin, G.; Tsymbal, V. (Одеські астрономічні публікації, 2008)
The results of spectropolarimetic study of one of the coolest Ap-stars Β CrB are presented. It was shown that effective magnetic fields measured in different spectral lines and folded in phase with the rotational period of the star significantly differ from each other in amplitudes and mean values of the magnetic field curves.